MOBILE APPLICATION DESIGN “GROSIRKEUN”TO IMPROVE MICRO SMALL AND MEDIUM ENTERPRISES (MSMEs) PRODUCTIVITY DURING THE COVID-19 PANDEMIC BASED ON E-COMMERCE - Topan, Ibnu; Neu, Fikri Rahmat Ramadhan; Hafiffudin, Ahmad Rizki; Saleh, Sulaiman; Rahmansyah, Deandro Fitra; Nugraha, Ucu (CENTRAL ASIA AND THE CAUCASUS, 2022)
At this time, there are many MSME actors who have had an impact on the Covid- 19 pandemic, especially in the middle to lower wholesale stall sector, they have a lot of difficulty in shopping for shop needs, especially during the current pandemic where social activities are limited. For this reason, the purpose of designing this Mobile Application is expected to help the MSME sector in shopping more efficiently based on the nearest location and can be delivered directly by the seller. The method used in designing this application is by using the Extreme Programming Method based on the Kotlin programming language which is connected to the MySQL database. The results of this study are an e-commerce-based mobile application where all transaction processes become easier and can solve problems of transaction difficulties during a pandemic, because users no longer need to access the website on a computer to make transactions, they only need gadgets such as smartphones. And can directly choose the region where he lives according to the available sellers, this will certainly help streamline time in ordering and selling users.